2021
DOI: 10.1111/1750-3841.16007
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial activity as an indicator of scallop (Mizuhopecten yessoensis) adductor muscle in early cold storage

Abstract: The purpose of this study was to reveal the role of mitochondria in indicating a change in the freshness of the adductor muscle of Mizuhopecten yessoensis during cold storage and hardening. The adductor muscle hardens after 96 h of cold storage and reaches the maximum degree of hardening in 6 h. In this study, after hardening (102 h), the muscle fiber structure obviously broke and curled, and the sarcomere structure disappeared at 150 h. After hardening (102 h), the morphology of the mitochondria changed, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Ivanina et al , used TPP+ to detect changes in scallop mitochondrial membrane potential and to evaluate the physiological changes in scallops during hypoxia–reoxygenation. In our previous study, we also found that mitochondrial changes could effectively indicate the freshness changes of scallop adductor muscle during cold storage …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Ivanina et al , used TPP+ to detect changes in scallop mitochondrial membrane potential and to evaluate the physiological changes in scallops during hypoxia–reoxygenation. In our previous study, we also found that mitochondrial changes could effectively indicate the freshness changes of scallop adductor muscle during cold storage …”
Section: Introductionmentioning
confidence: 85%
“…In our previous study, we also found that mitochondrial changes could effectively indicate the freshness changes of scallop adductor muscle during cold storage. 14 Tandem mass tag (TMT)-labeled proteomic analysis is the systematic assessment of all proteins expressed in a particular cell, tissue, biological fluid, or organism over a given period of time. TMT involves in vitro isotope labeling of peptides relative to absolute quantification and is a high-throughput screening technique in quantitative proteomics.…”
Section: Introductionmentioning
confidence: 99%